Saposin B–Deficient Metachromatic Leukodystrophy Mimicking Acute Flaccid Paralysis - Madaan, Priyanka; Jauhari, Prashant; Chakrabarty, Biswaroop; Kumar, Atin; Gulati, Sheffali (Neuropediatrics, 2019)
Metachromatic leukodystrophy (MLD) is a rare sphingolipid storage disorder caused by arylsulfatase A (ARSA) deficiency, resulting in central and peripheral demyelination. However, an uncommon form of MLD caused by saposin B deficiency is also described (around 10 mutations reported till date). MLD is a systemic disorder affecting the central and peripheral nervous system, gall bladder, and kidneys. Acute flaccid paralysis as the initial clinical presentation is previously known in ARSA-deficient MLD. Hereby, we report a child with acute flaccid paralysis with brain magnetic resonance imaging showing nonspecific periventricular leukodystrophy. He had progressive cognitive decline with gall bladder polyposis. ARSA levels were within normal limits. Leukodystrophy gene panel revealed a homozygous pathogenic deletion (Lys227del variant) in prosaposin (PSAP) gene. Hence, a final diagnosis of saposin B–deficient MLD was established. The index case highlights the importance of clinical and electrophysiological clues in the diagnosis of such atypical presentations of MLD.
Keywords: metachromatic leukodystrophy; saposin B; peripheral neuropathy; acute flaccid paralysis; gall bladder polyposis